Analisis Perencanaan Sumber Daya Manusia Kesehatan dengan Metode WISN di IGD dan Instalasi Hemodialisa RSUD Dr. Darsono Kabupaten Pacitan - Putranto, Johan Tri; Agus Sudarya; Joko Rizkie Widokarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The Workload Indicator Staff Need (WISN) method is a resource management tool used to calculate workforce needs based on the workload for certain types of workers, especially in the health sector. This study aims to analyze health human resources in the Emergency Installation and Hemodialysis Room of dr. Darsono Hospital, Pacitan Regency in 2024. The research design used was to conduct direct observation of health workers and document review to obtain the amount of time spent on each activity pattern of implementing staff in the Emergency Installation and Hemodialysis Room of dr. Darsono Hospital. Observations used work sampling techniques. The population and sample in this study were 30 health workers who worked in the Emergency Installation and Hemodialysis Room. Data analysis in this study used WISN analysis. The results of the study show that in the Emergency Installation there is still a shortage of health workers of 12 people, while in the Hemodialysis Room there is a shortage of health workers of 34 people. This study can be concluded that there is an influence between available working time, health worker activities, workload standards, slack factors, and calculations of health workers in the Emergency Installation and Hemodialysis Room, so that the hospital that oversees both services is advised to make improvements in terms of the division of health worker tasks. Keywords: WISN, Health Human Resources, Hospital